1996
DOI: 10.2355/isijinternational.36.1439
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Properties of Sinter with Fine Dispersed Pores at High Temperatures of 1273K and Above.

Abstract: ,nsc'co.i p' 1 oo Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…The reduction behavior changes greatly in this temperature range because a molten slag closes the pores in iron ore. Therefore, many researches [10][11][12][13][14] on the reducibility of iron ore and sinter have been carried out at the temperature which molten slag exists. However, the effect of the pore blockage on the reducibility is not so clear since most of reduction experiments have been conducted using the sinter or pellet, which have heterogeneous structures and phases, and the pore blockages were accompanied by phase changes when the slag in the sinter or pellet melted.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction behavior changes greatly in this temperature range because a molten slag closes the pores in iron ore. Therefore, many researches [10][11][12][13][14] on the reducibility of iron ore and sinter have been carried out at the temperature which molten slag exists. However, the effect of the pore blockage on the reducibility is not so clear since most of reduction experiments have been conducted using the sinter or pellet, which have heterogeneous structures and phases, and the pore blockages were accompanied by phase changes when the slag in the sinter or pellet melted.…”
Section: Introductionmentioning
confidence: 99%
“…48) Recent results suggested that it is possible to further improve the permeability of a sinter blend, and therefore control the pore size distribution of the sinter product, by adjusting the particle sizes of both limestone and coke breeze simultaneously. 49) …”
mentioning
confidence: 99%
“…Demonstration of the pore size distribution by the volume occupied by pores of certain size appears less informative: over 85-90% of the porosity volume belongs to very few pores larger than 500 µm. The frequency distributions are right-skewed with single peaks for a pore diameter of about 200 µm for almost all types of sinter, which is quite close to the average size of the pores in the range 148-159 µm (Hosotani et al, 1996), though data for open and closed pores were not distinguished in the given reference.…”
Section: Sintering -Methods and Products 226mentioning
confidence: 87%
“…This result might be explained by much higher porosity level observed for the sinter with basicity of 0.8. Positive effect of sinter porosity on its reducibility has been stated by many authors (Higuchi et al, 2004;Hosotani et al, 1996;Bhagat et al, 2006).…”
Section: Sintering -Methods and Products 230mentioning
confidence: 99%